XPS and SEM of unpolished and polished FeS surface - Mandrino, Djordje (Materiali in tehnologije, 2011)
It was attempted to measure parameters of Fe 2p and S 2p transitions for Fe and S in FeS to compare them with range of values obtainable from the literature FeS specimen was manufactured from the standard material used for chemical analysis. X-ray Photoelectron spectroscopy (XPS) was first performed on non-polished and then on polished surface. Scanning Electron Microscopy (SEM) was used to image both surfaces. It was found that major constituents of non-polished surface are sulphate and sulphite compounds but that composition and structure of the polished surface are also complex and may become increasingly so after cleaning by ion sputtering. At best, composition of the surface approximated FeS very poorly, thus necessitating the use of literature Fe 2p and S 2p parameter values instead of directly measuring improved values.
Keywords: železov sulfid; rentgenska fotoelektronska spektroskopija; elektronska mikroskopija; jedkanje; površine; reaktivnost